Scripture in the Search for the Doctrine of God : Reading and Receiving the Bible in Christian Tradition. Essays in Honor of D.H. Williams - Brumback III, Richard A.,; Fogleman, Alex, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026., 2026)
Scripture and the Search for the Christian Doctrine of God examines the dynamic exegetical traditions that shaped the fourth-century Trinitarian controversies and how these legacies of biblical reading have influenced both evaluations of the fourth century and subsequent use of patristic materials by scholars and theologians. Part I, "Legacies," focuses on pre-Nicene reading practices with an eye towards how they were received in the fourth century and beyond. Part II, "Traditions," investigates how fourth- and fifth-century theologians received and inherited pre-Nicene traditions of biblical reading. Part III, "Receptions," highlights the way that patristic exegesis has been received in a variety of post-patristic contexts, including Medieval Chinese Christianity, early Renaissance Humanism, and Contemporary Evangelicalism. The result is a greater appreciation of the deeply biblical character of the early Christian search for the doctrine of God.